BRIDGING THE GAP IN ACNE MANAGEMENT: A NARRATIVE REVIEW OF CURRENT THERAPIES AND THE EMERGENCE OF CLASCOTERONE - Piasecka, Joanna; Gołembiewski, Bartosz; Mulski, Grzegorz; Manicka, Martyna; Baranowicz, Michał; Mazurkiewicz, Weronika; Borecka, Zuzanna; Sobczak, Agnieszka Marta; Szymczak, Alicja; Jaworowicz, Anna (International Journal of Innovative Technologies in Social Science, 2026)
Acne vulgaris is one of the most common dermatological conditions worldwide, estimated to affect up to 85–90% of the population at some point in their lives. While most frequently observed in adolescents and young adults, an increasing number of patients over the age of 25- long after the period of puberty- are presenting with this problem. The pathogenesis of acne is complex, involving sebaceous gland hyperactivity, follicular hyperkeratosis, excessive proliferation of Cutibacterium acnes, and inflammation, all of which lead to a disruption of skin homeostasis. The causes of this deregulation are primarily attributed to hormonal imbalances, particularly the influence of androgens, as well as carbohydrate metabolism dysfunction and chronic stress. For decades, several groups of medications have been used interchangeably, including isotretinoin, hormonal contraceptives, antibiotics, spironolactone, and various topical agents. Although these treatments have proven effective in many cases, a significant proportion of patients still face side effects, lack of clinical improvement, or disease recurrence. After many years without the introduction of any innovative medication, a new option has emerged for patients struggling with acne vulgaris: clascoterone. Its mechanism of action consists of blocking androgen receptors in the skin, which suppresses sebaceous gland hyperactivity and reduces inflammation. As a topical preparation, it carries a much lower risk of systemic side effects than oral treatments. In this article, we aim to present this new drug in comparison to currently available therapeutic options, looking forward to a potential breakthrough in the treatment of this common dermatosis.